Trading information goods on a network: An experiment - Nobuyuki Hanaki; Yutaka Kayaba; Jun Maekawa; Hitoshi Matsushima (Osaka University, Institute of Social and Economic Research (ISER), 2021)
We experimentally examine the impact of a cycle path on the trading of a copyable information good in networks. A cycle path in a network permits a buyer to become a reseller that can compete against existing sellers by replicating the good. Theory predicts that the price of the information good, even with the first transaction where there is not yet a reseller competing with the original seller, will be lower in networks with a cycle path than otherwise. However, our experiment reveals that the observed price for the first transaction is significantly higher in networks with a cycle path.
Keywords: D42; L14; 330; Information good; Network